Water Quality Assessment, Antibiotic Resistance and Plasmid Profiles of Bacteria Isolated from Asa River, Ilorin, Nigeria - Sule, Ismaila Olawale; Adekunle, Olutoyin Catherine; Adebesin, Ibrahim Olakunle; Abdulsalam, Zainab Biola; Oladunjoye, Olatunji Iyiola; Muhammed, Mariam (Iraqi Journal of Science, 2023)
Bodies of water are usually being polluted by wastes from domestic and industrial sources thereby making them unfit for use. Hence, this study aimed at assessing the water quality from Asa River, Ilorin, Nigeria in terms of bacteriological and physicochemical parameters. The bacteriological parameters assessed were heterotrophic bacterial count, total coliform, faecal coliform, identification of the isolates, antibiotic resistance patterns, and plasmid profile of the isolates. Whereas, the assessed physicochemical parameters were pH, total chloride, suspended solid, and total hardness. The heterotrophic bacterial count, total coliform, and faecal coliform counts ranged from 7.6 x 103 to 3.2 x 106 cfu/ml, 9 to 24000 MPN/ 100ml and 0 to 6.0 x 103 cfu/ml respectively. Bacteriological analysis showed that the water contained arrays of bacteria heavily contaminated with pathogens. The genera of bacteria isolated were Escherichia, Pseudomonas, Brevundimonas, Enterococcus, Burkholderia, Enterobacter, Proteus, Pasteurella and Aeromonas. The pH, total hardness, total chloride, and suspended solids of the water ranged from 6.2 to 7.9, 128 to 291 mg/l, 6.21 to 17.04 mg/l and 170 to 310 mg/l respectively. All the Gram-negative bacteria were resistant to cefuroxime, cefixime, augmentin, and ceftazidime. Whereas all the Gram-positive bacteria were resistant to cefuroxime, cloxacillin, augmentin, and vancomycin. The bacteria also showed multiple antibiotic resistance. The resistance of Pasteurella multocida to nitrofurantoin was plasmid mediated. After plasmid curing, Brevundimonas diminuta was susceptible to ciprofloxacin and intermediately susceptible to gentamicin, while Pseudomonas fluorescens was susceptible to ofloxacin and ceftazidime and intermediately susceptible to ciprofloxacin. It was concluded that the water from Asa River at the different sampling points was unsafe in term of bacteriological as well as some physicochemical qualities. It is recommended that this water should not be used in its present state without treatment. Discharge of industrial, agricultural and domestic wastes should be stopped; and open defecation at the bank of this river should be discouraged.